Association Between Depression, Health Beliefs, and Face Mask Use During the COVID-19 Pandemic - Bressington, Daniel Thomas; Cheung, Teris Cheuk Chi; Lam, Simon Ching; Suen, Lorna Kwai Ping; Fong, Tommy Kwan Hin; Ho, Hilda Sze Wing; Xiang, Yu-Tao (Frontiers in Psychiatry, 2020)
The 2019 novel coronavirus (COVID-19) pandemic is associated with increases in psychiatric morbidity. It is unclear if similar rates are evident outside of mainland China or if people with depressive symptoms understand or apply COVID-19 information and face mask use guidelines differently to the general population. Therefore, this study aimed to examine associations between depression, health beliefs and face mask use during the COVID-19 pandemic among the general population in Hong Kong. This study gathered data from 11,072 Hong Kong adults via an online survey. Respondents self-reported their demographic characteristics, depressive symptoms (PHQ-9), face mask use, and health beliefs about COVID-19. Hierarchical logistic regression was used to identify independent variables associated with depression. The point-prevalence of probable depression was 46.5% (n=5,150. Respondents reporting higher mask reuse (OR=1.24, 95%CI 1.17-1.34), wearing masks for self-protection (OR=1.03 95%CI 1.01-1.06), perceived high susceptibility (OR=1.15, 95%CI 1.09-1.23) and high severity (OR=1.33, 95%CI 1.28-1.37) were more likely to report depression. Depression was less likely in those with higher scores for cues to action (OR=0.82, 95%CI 0.80-0.84), knowledge of COVID-19 (OR=0.95, 95%CI 0.91-0.99) and self-efficacy to wear mask properly (OR=0.90 95%CI 0.83-0.98). We identified a high point-prevalence of probable major depression and suicidal ideation during the COVID-19 outbreak in Hong Kong. The findings highlight that COVID-19 health information may be a protective factor of probable depression and suicidal ideation during the pandemic. Accurate and up-to-date health information should be disseminated to vulnerable subpopulations, perhaps using digital health technology and social media platforms to prompt professional help-seeking behaviour.